2017
DOI: 10.1089/ars.2016.6803
|View full text |Cite
|
Sign up to set email alerts
|

Redox and Peroxidase Activities of the Hemoglobin Superfamily: Relevance to Health and Disease

Abstract: Significance: Erythrocyte hemoglobin and myocyte myoglobin, although primarily oxygen carrying proteins, have the capacity to do redox chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 132 publications
(125 reference statements)
0
20
0
Order By: Relevance
“…Here, we extend this concept by showing that eNOS can reduce globin proteins, including α-globin (bound to AHSP), Cygb, and neuroglobin (data not shown). This finding may have broad implications, considering that the related proteins inducible NOS (iNOS) and neuronal NOS (nNOS) could also modulate the redox states of Cygb and neuroglobin to regulate their functions in various tissues (47).…”
Section: Table 1 Pe Dose Responses For Vasoconstriction Of Isolated mentioning
confidence: 99%
“…Here, we extend this concept by showing that eNOS can reduce globin proteins, including α-globin (bound to AHSP), Cygb, and neuroglobin (data not shown). This finding may have broad implications, considering that the related proteins inducible NOS (iNOS) and neuronal NOS (nNOS) could also modulate the redox states of Cygb and neuroglobin to regulate their functions in various tissues (47).…”
Section: Table 1 Pe Dose Responses For Vasoconstriction Of Isolated mentioning
confidence: 99%
“…Pseudo-peroxidases are different in terms of their heme and activity characteristics, but all of them have one common feature: exposure to H 2 O 2 causes immediate oxidation of protein amino acids that are close to the active center (most commonly tyrosine, tryptophan, or histidine) [ 62 , 63 ]. Compound I was not detected for pseudo-peroxidases.…”
Section: Diversity Of Human Hemoproteins With Peroxidase Activitymentioning
confidence: 99%
“…Under some pathological conditions, particularly as a result of microangiopathic hemolytic anemia, concentrations of Hb in plasma can reach micromolar levels [ 149 ]. Under uncontrolled pathological conditions accompanied by inflammation and oxidative stress, depletion of antioxidants and generation of superoxide radicals by activated neutrophils induce the redox activity of the hemoproteins, resulting in damage to plasma proteins and lipids [ 62 ]. The globin-based free radicals of ferryl hemoglobin were detected in normal human blood upon H 2 O 2 treatment [ 150 ].…”
Section: Hemoglobin and Myoglobinmentioning
confidence: 99%
“…It is a dynamic mediator in the maintenance of redox homeostasis and performs the activities of peroxidase and nitric oxide dioxygenase (NOD), which catalyzes nitric oxide (NO) or nitrite to nitrate in rat hepatocytes. [11][12][13][14] Emerging evidences indicated that Cygb is negatively associated with liver fibrosis and HCC tumorigenesis via regulating oxidative stress pathways. [15][16][17][18][19] Cygb absence accounts for a high incidence of multiple malignancies including liver, lung and colon cancer and lymphoma in aged Cygb −/− mice, compared with wide-type mice.…”
Section: The Interaction Of Ons Withmentioning
confidence: 99%
“…Cytoglobin is a ubiquitously expressed hexacoordinate hemoglobin. It is a dynamic mediator in the maintenance of redox homeostasis and performs the activities of peroxidase and nitric oxide dioxygenase (NOD), which catalyzes nitric oxide (NO) or nitrite to nitrate in rat hepatocytes . Emerging evidences indicated that Cygb is negatively associated with liver fibrosis and HCC tumorigenesis via regulating oxidative stress pathways .…”
Section: Introductionmentioning
confidence: 99%